Analysis of Working Capital Efficiency and BOPO in Improving ROE and ROA at Bank Syariah Indonesia for the Period 2021–2023 - Alhidayatullah (At-Tamwil: Journal of Islamic Economics and Finance, 2025)
The importance of efficient working capital management and operational cost control to improve the financial performance of banking companies. Return on Equity (ROE) and Return on Assets (ROA) are the main indicators in assessing a bank's profitability, so it is necessary to analyze the factors that affect it, especially working capital efficiency and the ratio of BOPO (Operating Costs to Operating Income). The purpose of this study is to analyze the level of working capital efficiency of Bank Syariah Indonesia (BSI) during the 2020–2023 period, examine its effect on ROA and ROE, and assess the impact of consolidation on working capital efficiency and profitability of BSI. The method used is quantitative with a descriptive and verifiable approach. The data used is secondary data from Bank Syariah Indonesia's annual financial statements for the 2021–2023 period. The data collection technique is carried out through documentation, while the data analysis technique uses multiple linear regression with the help of SPSS. The results of the study showed that there was no significant effect of working capital efficiency on ROE and ROA, as well as BOPO there was no significant influence on ROE and ROA. The contribution of this research is to provide strategic input for bank management to improve financial performance through working capital optimization and operational cost efficiency. In addition, this research can also be a reference for investors in assessing the financial health of banks.